PROS AND CONS OF ONLINE COURSES IN THE EDUCATIONAL PROCESS - FAYZULLAEVA, Madina (Journal of Pedagogical and Psychological Studies, 2023)
This article is related to the introduction of online courses into the educational process. The main goal of the article is to identify the positive and negative aspects of online education. The importance and value of online education in the conditions of Uzbekistan is analyzed. As with everything, there are pros and cons, and this article discusses some of the issues with online education.